Studi potensi ruang terbuka publik berbasis preferensi masyarakat di Kecamatan Turen Kabupaten Malang - Lury Yusiana; Made Dirdaedrea Dharma Rinasa (Jurnal Arsitektur Lansekap, 2025)
Turen District is one of the administrative regions in Malang Regency that has an area of 63.60 km2. This region does not have adequate public open space (POS) to meet the social and cultural needs of its community. As a result, the community lacks space to gather, exercise, and express their identity. This study aims to identify potential land for developing POS at the district scale and to find out what facilities are needed and expected by the community. The analysis method used was descriptive statistics using Ordinal Scale and Guttman Scale to determine the priorities and preferences of the community. Location A was one of the three potential POS locations in Turen District that had an area of 2.4 ha and was located in Turen Village. The research results showed Location A as a strategic location with accessibility priority of the community using private vehicles. In addition, the community wanted POS that could support recreational activities, social interaction, and self-development. The facilities that were the main priority of the community were jogging track, plaza area, children’s playground, and culinary. The recommendation given was to design POS with the concept of Civic Landscape that involved community participation and prioritized the principle of social justice for all groups.